A Census of Southern Pulsars at 185 MHz. (20th December 2017) - Xue, Mengyao; Bhat, N. D. R.; Tremblay, S. E.; Ord, S. M.; Sobey, C.; Swainston, N. A.; Kaplan, D. L.; Johnston, Simon; Meyers, B. W.; McSweeney, S. J.
Abstract: The Murchison Widefield Array, and its recently developed Voltage Capture System, facilitates extending the low-frequency range of pulsar observations at high-time and -frequency resolution in the Southern Hemisphere, providing further information about pulsars and the ISM. We present the results of an initial time-resolved census of known pulsars using the Murchison Widefield Array. To significantly reduce the processing load, we incoherently sum the detected powers from the 128 Murchison Widefield Array tiles, which yields 10% of the attainable sensitivity of the coherent sum. This preserves the large field-of-view ( 450 deg 2 at 185 MHz), allowing multiple pulsars to be observed simultaneously. We developed a WIde-field Pulsar Pipeline that processes the data from each observation and automatically folds every known pulsar located within the beam. We have detected 50 pulsars to date, 6 of which are millisecond pulsars. This is consistent with our expectation, given the telescope sensitivity and the sky coverage of the processed data ( 17 000 deg 2 ). For 10 pulsars, we present the lowest frequency detections published. For a subset of the pulsars, we present multi-frequency pulse profiles by combining our data with published profiles from other telescopes. Since the Murchison Widefield Array is a low-frequency precursor to the Square Kilometre Array, we use our census results to forecast that a survey using the low-frequency component of the Square Kilometre Array Phase 1 can potentially detect around 9 400 pulsars.